Transient Groundwater Flow Through a Coastal Confined Aquifer and Its Impact on Nearshore Submarine Slope Instability. Issue 9 (28th August 2020) - Sultan, N.; Garziglia, S.; Bompais, X.; Woerther, P.; Witt, C.; Kopf, A.; Migeon, S.
Abstract: Rare in situ pore pressure and temperature data sets collected over more than one decade in a submarine landslide‐prone area off Nice (Southeast France) have been used to characterize a transient groundwater exchange between a coastal confined aquifer and the nearshore shallow‐water submarine shelf. The near‐coast study zone is highly exposed to geohazards and remains sadly famous for the 1979 catastrophic tsunamigenic submarine landslide with several casualties and substantial material damage. Measured pore pressure buildup does not appear to be synchronized with either the discharge of the nearby Var River or with precipitation in the Nice area. Unexpectedly, pore pressure fluctuations synchronizes well with seabed temperature trends indicating that the nearshore submarine shelf is mainly impacted by long smooth seasonal variations. We used the pore pressure and temperature data to describe the general transport mechanisms of pore waters and show that pore pressure diffusion is predominantly responsible for the near‐seabed pore pressure buildup. Based on our results and previously published geotechnical data, slope stability calculations reveal that groundwater exchange has a major impact on slope instability and shear zone formation in a prone‐to‐failure area. Minor earthquake‐induced ground accelerations seem to contribute to the nearshore slope instability by decreasing its factor of safety. Key Points: A decade of pore pressure data reveals important groundwater exchange between a coastal aquifer and a nearshore submarine shelf Excess pore pressures are more likely the trigger of observed shear zones in a prone‐to‐failure area Earthquakes could accelerate the development of progressive slope failure by decreasing its factor of safety